Pengembangan Desain Kemasan Produk sebagai Marketing untuk Meningkatkan Daya Tarik Pelanggan pada UMKM Mie Goreng Zaitun - Ita Purnama; Rabiahtun Adwiyyah; Yuwidasari Yuwidasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Packaging is one of the spearheads of a product's sales. Packaging has a very important role because it will always be related to the packaged commodity and at the same time is the selling value and image of the product. This selling value increases when the resulting product gets added value from attractive packaging. While the product image related to the image of the product in the minds of consumers will be better if the product is packaged well, in other words the product can give a good impression to consumers. The development of product packaging design for UMKM actors in Bima City is to provide insight into new packaging designs and forms that make products more valuable and safe.